Studying Nitrocellulose Decomposition Process in Nitrocellulose-Cellulose-Trinitrotoluene System - Khuong, Pham Van; Vu, Hoang The; Tuong, Nguyen Manh (VNU Journal of Science: Natural Sciences and Technology; Vol 42 No 1DO - 10.25073/2588-1140/vnunst.5869, 2025)
This study presents the results of determining the kinetic parameters of the decomposition process of system Nitrocellulose-Cellulose-Trinitrotoluene. The kinetic parameters were determined based on differential scanning calorimetry (DSC) data using the Kissinger and Ozawa methods of NC in the samples of NC, NC-Cellulose, NC-Trinitrotoluene dissolved in solution, molten NC-Trinitrotoluene, NC-Cellulose-Trinitrotoluene, NC-Cellulose-Trinitrotoluene-DPA, NC-Cellulose-Trinitrotoluene-Centralite No. 1, NC-Cellulose-Trinitrotoluene-Centralite No. 2. The degree of thermal decomposition of the samples of NC-Cellulose-Trinitrotoluene containing chemical stabilizers such as DPA, Centralite No. 1, Centralite No. 2 was evaluated by measuring the gas pressure over time of the decomposition products.